2018
DOI: 10.3390/molecules23040826
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology for Cancer Therapy Based on Chemotherapy

Abstract: Chemotherapy has been widely applied in clinics. However, the therapeutic potential of chemotherapy against cancer is seriously dissatisfactory due to the nonspecific drug distribution, multidrug resistance (MDR) and the heterogeneity of cancer. Therefore, combinational therapy based on chemotherapy mediated by nanotechnology, has been the trend in clinical research at present, which can result in a remarkably increased therapeutic efficiency with few side effects to normal tissues. Moreover, to achieve the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
138
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(139 citation statements)
references
References 241 publications
(267 reference statements)
0
138
0
1
Order By: Relevance
“…For example, the results of the present study indicated that IQGAP1 is a potential target for CRC treatment and further highlighted that miR-124 is in theory a potential way to antagonize IQGAP1 similar to the WW domain peptide of IQGAP1 mentioned. Recently, nanoparticles have emerged as a popular concept for targeted delivery of therapeutic agents to tumors (37)(38)(39). A type of combined polymeric nanoparticle (PNP) entrapping phosphatidyl inositol 3 kinase inhibitors or irinotecan suppresses or even eliminates lung metastasis of CRC in a BALB/C mice model, but negligible accumulation of PNPs is detected in the organs including the spleen, liver and kidneys indicating good tissue selectivity of PNPs and organ safety (40).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the results of the present study indicated that IQGAP1 is a potential target for CRC treatment and further highlighted that miR-124 is in theory a potential way to antagonize IQGAP1 similar to the WW domain peptide of IQGAP1 mentioned. Recently, nanoparticles have emerged as a popular concept for targeted delivery of therapeutic agents to tumors (37)(38)(39). A type of combined polymeric nanoparticle (PNP) entrapping phosphatidyl inositol 3 kinase inhibitors or irinotecan suppresses or even eliminates lung metastasis of CRC in a BALB/C mice model, but negligible accumulation of PNPs is detected in the organs including the spleen, liver and kidneys indicating good tissue selectivity of PNPs and organ safety (40).…”
Section: Discussionmentioning
confidence: 99%
“…During the past years, nanotechnology-based diagnostic and therapeutic systems have provided potential solutions for cancer treatments. [10][11][12][13] Multifunctional nanosystems (NSs) in conjugation with various imaging probes and targeting agents such as antibodies (Abs)/aptamers (Aps), and enzymes have been recently developed for cancer therapy. [14][15][16] Among different types of NSs, the greater affinity, specificity, and functionality of enzymes to selectively target the desired cells/tissues make them prominent treatment modalities for a variety of diseases.…”
Section: Synthesis Of Peg Ligands Sh-peg-coohmentioning
confidence: 99%
“…Nanotechnology often overcomes the chemotherapy associated issues [8]. Nanotechnologybased carriers primarily aimed to improve the therapeutic efficacy of anticancer agents by increasing bioavailability, solubility, and retention time at the tumor sites.…”
Section: Introductionmentioning
confidence: 99%